Relief of Neuropathic Pain After Spinal Cord Stimulator Implantation in a Patient With Idiopathic Thoracic Transverse Myelitis: A Case Report. Issue 11 (1st December 2019) - Reddy, Rajiv; Prasad, Rupa; Rejai, Sepehr; Halter, Kenneth; Chen, Jeffrey
Abstract : Transverse myelitis (TM) is a rare neurologic disorder of acute inflammation resulting in spinal cord injury. Chronic pain in TM is a significant detriment to quality of life. Spinal cord stimulation (SCS) is an emerging treatment that has shown significant efficacy in neuropathic pain. We present a 37-year-old man with a history of idiopathic thoracic TM and refractory chronic neuropathic pain who underwent an SCS trial. He reported 70% improvement during the trial and was subsequently implanted with an SCS. He continues to experience significant pain relief and functional improvement (>80%) with conventional paresthesia programming at the 9-month follow-up.